Teachers’ Lived Experiences in the Transition to the MATATAG Curriculum: A Phenomenological Inquiry into Adaptation, Challenges, and Growth - Torrefiel, Josephine; Cagape, Estelita; Galan, Onabelle; Doydora, Venice; Pintac, Tejie (Journal of Interdisciplinary Perspectives, 2025)
This study seeks to explore teachers' lived experiences in transitioning to the MATATAG Curriculum amidst inadequate instructional materials, limited time for teaching, the diverse needs of learners, lack of teacher training, unclear implementation guidelines, heightened levels of stress, and the necessity to innovate in teaching. Using a phenomenological approach, in-depth interviews with teachers from selected schools in Candijay, Bohol, were conducted to gain insight into challenges, strategies of adaptation, and professional growth. These have demonstrated that the curriculum was implemented inconsistently because of the vague guidelines and poor training, forcing the teachers to fall back on the old instructional materials and teaching methods. Again, the limitation in instructional time constrained their capacity to deliver quality education. Moreover, teachers found it hard to meet the diverse needs of learners due to insufficient resources and training. The study has underlined the requirement for more explicit curriculum guidelines, government support, enhanced teacher training, mental health interventions, and innovative teaching strategies. These challenges are aligned with UN SDG-4 on Quality Education, which ensures that educators and students experience inclusive, equitable, and effective learning. Strengthening systemic support will enhance the MATATAG Curriculum's sustainability and impact on Philippine education.